Portuguese Version of the Pain Beliefs and Perceptions Inventory: a Multicenter Validation Study - Azevedo, LF (2017)
Background: We aimed to perform the translation, cultural adaptation, and validation of the Pain Beliefs and Perceptions Inventory (PBPI) for the European Portuguese language and chronic pain population. Methods: This is a longitudinal multicenter validation study. A Portuguese version of the PBPI (PBPI-P) was created through a process of translation, back translation, and expert panel evaluation. The PBPI-P was administered to a total of 122 patients from 13 chronic pain clinics in Portugal, at baseline and after 7 days. Internal consistency and test-retest reliability were assessed by Cronbach's alpha (α) and intraclass correlation coefficient (ICC). Construct (convergent and discriminant) validity was assessed based on a set of previously developed theoretical hypotheses about interrelations between the PBPI-P and other measures. Exploratory and confirmatory factor analyses were performed to test the theoretical structure of the PBPI-P. Results: The internal consistency and test-retest reliability coefficients for each respective subscale were α = 0.620 and ICC = 0.801 for mystery; α = 0.744 and ICC = 0.841 for permanence; α = 0.778 and ICC = 0.791 for constancy; and α = 0.764 and ICC = 0.881 for self-blame. Exploratory and confirmatory factor analysis revealed a four-factor structure (performance, constancy, self-blame, and mystery) that explained 63% of the variance. The construct validity of the PBPI-P was shown to be adequate, with more than 90% of the previously defined hypotheses regarding interrelations with other measures confirmed. Conclusion: The PBPI-P has been shown to be adequate and to have excellent reliability, internal consistency, and validity. It may contribute to a better pain assessment and is suitable for research and clinical use.